2010
DOI: 10.1111/j.1471-4159.2010.06803.x
|View full text |Cite
|
Sign up to set email alerts
|

Intersection between metabolic dysfunction, high fat diet consumption, and brain aging

Abstract: J. Neurochem. (2010) 114, 344–361. Abstract Deleterious neurochemical, structural, and behavioral alterations are a seemingly unavoidable aspect of brain aging. However, the basis for these alterations, as well as the basis for the tremendous variability in regards to the degree to which these aspects are altered in aging individuals, remains to be elucidated. An increasing number of individuals regularly consume a diet high in fat, with high‐fat diet consumption known to be sufficient to promote metabolic dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 305 publications
(254 reference statements)
2
61
0
2
Order By: Relevance
“…Studies from our laboratory and others' have demonstrated that HFDs exacerbate tissue dysfunction in aging animals (11,29,46,68,76). Additionally, studies from our laboratory and others' have shown that HFDs promote much greater amounts of adipose gain, and presumably adipose tissue dysfunction, compared with younger animals (46,50,66). These data point to important, and as yet unknown, interactions between obesity and aging.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies from our laboratory and others' have demonstrated that HFDs exacerbate tissue dysfunction in aging animals (11,29,46,68,76). Additionally, studies from our laboratory and others' have shown that HFDs promote much greater amounts of adipose gain, and presumably adipose tissue dysfunction, compared with younger animals (46,50,66). These data point to important, and as yet unknown, interactions between obesity and aging.…”
Section: Discussionmentioning
confidence: 67%
“…Because of the potential for age-related changes in adipose function to modulate overall health and promote metabolic disease, there is a growing interest in studying aging adipose tissue. White adipose tissue is recognized as an important modulator of multiple physiological processes and is strongly linked to the development of multiple morbidities (8,16,46,66,76). The ability of adipose tissue to exert these effects comes from alterations in the endocrine functions of adipose (22,52,71) as well as the contributions of adipose tissue to glucose and lipid homeostasis (10,26,37,75).…”
mentioning
confidence: 99%
“…Increased inflammatory signaling, adipokine levels, oxidative or nitrostative stress, mitochondrial dysfunction, and lipid metabolism have all been shown to occur with HF feeding (13,27, reviewed in Ref. 52). Some of these peripheral effects, such as oxidative stress, also occur in the brain following HF feeding (21,40,58), and HF feeding increases cognitive impairment, tau deposition, MPTP vulnerability, and inflammation in the brain (15,38,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In addition metabolic disorders, such as dyslipidaemia and hyperinsulinaemia, increase with age. 5 Thus, when investigating the metabolic impact of dietary or other interventions using experimental animal models, it is essential to take into consideration the age of the animals in order to interpret the results. 6 The aim of this study was to test the impact of age on the changes in lipid and glucose homeostasis in young and middle-aged mice receiving a high-fat diet (HFD).…”
mentioning
confidence: 99%